Socio-Economic Analysis of Women's Participation in Silk Industry in Bihar - Ruksar AHMAD; Saneem FATIMA (International Journal of Environmental, Sustainability and Social Science, 2025)
This study explores the role of rural women in sericulture, focusing on their involvement and challenges in the Tussar silk industry in Bihar, India. With a focus on four districts, Purnia, Katihar, Banka, and Bhagalpur, the study surveyed 120 women, 30 from each district, engaged in sericulture. Women constitute 60% of the workforce in sericulture, which contributes 28.41% of household income, making it a critical livelihood source in India. Their involvement is concentrated in activities close to home, as they face challenges in tasks requiring external mobility. Many women entrepreneurs in this sector have limited education, and there is a need for government and sericulture departments to collaborate on targeted training and development programs. These initiatives aim to uplift the socioeconomic conditions of rural women and enhance their participation in sericulture for economic empowerment.